Effect of admission and onset time on the prognosis of patients with cardiogenic shock - Behnes, Michael; Rusnak, Jonas; Egner-Walter, Sascha; Ruka, Marinela; Dudda, Jonas; Schmitt, Alexander; Forner, Jan; Mashayekhi, Kambis; Tajti, Péter; Ayoub, Mohamed; Weiß, Christel; Akın, Ibrahim; et al. (Chest, 2024)
Background - The spectrum of patients with cardiogenic shock (CS) has changed significantly over time. CS has become especially more common in the absence of acute myocardial infarction (AMI), while this subset of patients was typically excluded from recent studies. Furthermore the prognostic impact of onset time and onset place due to CS has rarely been investigated. - Research Question - Do the place of CS onset (out-of-hospital, ie, primary CS vs in-hospital, ie, secondary CS) and the onset time of out-of-hospital CS (ie, on-hours vs off-hours admission) affect the risk of all-cause mortality at 30 days? - Study Design and Methods - This prospective monocentric registry included consecutive patients with CS of any cause from 2019 until 2021. First, the prognostic impact of the place of CS onset (out-of-hospital, ie, primary CS vs during hospitalization, ie, secondary CS) was investigated. Thereafter, the prognostic impact of the onset time of out-of-hospital CS was investigated. Furthermore, the prognostic impact of causative AMI vs non-AMI was investigated. Statistical analyses included Kaplan-Meier analyses, and univariable and multivariable Cox regression analyses. - Results - Two hundred seventy-three patients with CS were included prospectively (64% with primary out-of-hospital CS). The place of CS onset was not associated with increased risk of all-cause mortality within the entire study cohort (secondary in-hospital CS: hazard ratio [HR], 1.532; 95% CI, 0.990-2.371; P = .06). However, increased risk of 30-day all-cause mortality was seen in patients with AMI related secondary in-hospital CS (HR, 2.087; 95% CI, 1.126-3.868; P = .02). Furthermore, primary out-of-hospital CS admitted during off-hours was associated with lower risk of all-cause mortality compared to primary CS admitted during on-hours (HR, 0.497; 95% CI, 0.302-0.817; P = .01), irrespective of the presence or absence of AMI. - Interpretation - Primary and secondary CS were associated with comparable, whereas primary out-of-hospital CS admitted during off-hours was associated with lower risk of all-cause mortality at 30 days. - Trial Registry - ClinicalTrials.gov; No.: NCT05575856; URL: www.clinicaltrials.gov
Online verfügbar: 12. August 2023, Artikelversion: 8. Januar 2024
Gesehen am 10.06.2024